Reaktualisasi Pendidikan Behavioristik - Faizatul Muazzaroh (STAI Syaichona Moh. Cholil Bangkalan, 2017)
As we all know that the problems in education are not over. Until finally various learning theories emerged as one of the solutions problematics solving in learning activities. Among the many theories that contribute much is the theory of Behavioristic learning. There are several figures that have contributed to the development of this theory, including: Ivan Pavlov with the theory of Clasical Conditioning, Edward Lee Thorndike with the theory of Connectionism, Burrhus Frederic Skinner with the theory of Operant Conditioning, John Broadus Watson with Conditioning theory, Edwin Ray Guthrie with the theory of Contiguous Conditioning Theory , and Carl Leonard Hull with Drive Reduction Theory.